Laypersons’ Perception Towards Gummy Smile and Facial Types: Acceptability and Treatment Benefit - Norman, Noraina Hafizan; Ahmad Othman, Anis Azyan; Azhar, Nur Atiff; Lim, Tong Wah; Mohamed Kassim, Zethy Hanum; Abdul Ghani, Sarah Haniza; Mahmud, Melati (Journal of Dentistry Indonesia, 2022)
Smile aesthetic perceptions could have different impact on orthodontic and prosthodontic treatment management and options to the patient. Objectives: To determine the laypersons’ smile aesthetic perceptions; irrespective of age and gender, of gummy smile and its treatment need and benefit on three different facial types. Methods: Smiling frontal photographs of a male and female subject were altered to simulate three facial types (brachyfacial, mesofacial and dolichofacial) with different levels of gummy smile increase from 2.0mm to 5.0mm. A total of 150 laypersons ranging from 18-45 years old were randomly approached to rate the photographs. Perceptions differences were assessed using visual analog scale for each group. Results: Repeated measure ANOVA was applied and showed that the mean level of attractiveness among three different facial types based on gummy smile levels was not statistically significant. This suggests that the facial type does not influence the laypersons’ ratings on gummy smile level. Further test found that the laypersons perceived 4.0mm gummy smile as borderline attractive while at 5.0mm is considered as unaesthetic. Chi Square test showed that there was statistically significant difference between the treatment need and attractiveness scoring (p=<0.01) whereby the treatment benefit is dependent on attractiveness ratings of gummy smile variables. Conclusion: Different levels of gingival show affect the laypersons’ perception of smile attractiveness, regardless of the facial type. The higher the level of gingival show, as seen in 4-5mm categories is perceived to be unattractive and thus, more likely to benefit from treatment.